Improving the Online Regional Student Experience : Findings from the Country Universities Centre (CUC) Student Evaluation. - Stone, Cathy; Crawford, Nicole; Ronan, Chris; Davis, Monica (Student Success v.13 n.2 p.32-41 https://doi.org/10.5204/ssj.2313, 2022)
For Australian university students living out of reach of a campus and studying online, the growing presence of Regional University Centres (RUCs) is changing their student experience for the better. People from regional areas of Australia are historically under-represented at university. Those who begin university are at higher risk of not completing their qualifications than students from metropolitan areas. COVID-19 restrictions in the past two years have added to the continued growth in regional students studying their degrees online. A recent survey of students attending a Country Universities Centre (CUC) within their local community shows these centres to be highly effective in supporting regional students. The participants overwhelmingly reported improvements not only in their academic progress and results, but also in their motivation, confidence, and likelihood of completing their qualification. [Abstract]